The Need Analysis of English for Specific Purpose in Faculty of Law - Fikri Asih Wigati; Candra Hayatul Iman (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The flow of globalization is inevitable. This has brought changes in the development of English for Specific Purpose. Responding to this condition, this study was conducted to determine the need analysis of ESP in faculty of Law, however this study focus on the undergraduates point of view. This research focused to students of Law Faculty in on state university in West Java, Indonesia by using qualitative research design. The data were obtained from several techniques, namely interview, and documentations. Based on the interview data, it was found that the expected materials for the ESP in Law Faculty are communication skills especially on speaking and writing to prepare themselves to serve their clients. In addition, grammar focus and pronunciation drilling are less interesting, they think that active learning activities are more engaging. Keywords: ESP, Law Faculty, students point of view